Freight Courier Payroll System in Islamic Law Review (Study on Id Express Way Halim Bandar Lampung) - Marwin, Marwin; Maraliza, Helma; Nugraha S, Muhammad Akbar (ASAS, 2023)
The more advanced about freight forwarding services in the modern era, many people now like to send goods through freight forwarding services such as one of Id Express to facilitate people in carrying out goods delivery activities, where consumers only pay service wages to the Id Express after a transaction where the determination of service wages is carried out by the Id Express. The focus of this research is how the practice of paying couriers for goods in Id Express and seen from the perspective of shari'ah economic law? The purpose of this study is to know and analyze the practice of paying couriers for goods in Id Express and seen from the perspective of shari'ah economic law. This research is a field research. The power collection methods used are; interviews and documentation. The collected data is then analyzed qualitatively with a descriptive approach to explain the entire wage system at Id Express Way Halim, Bandar Lampung. The results of this study found that the freight courier wage system on Id Express Way Halim is a wage system seen from the delivery of goods, where the courier must send goods according to the target given from the Id Express and if the couriers do not send packages according to the target, their salaries will be deducted by 50% from the Id Express, while the wage system is not explained at the beginning of the agreement between the courier and the company, so in Islamic Law it is not allowed because it is not in accordance with the print of the Qur'an surah Hud verse 85, then does not meet the requirements of ijarah which is the willingness of both parties. And not in accordance with Consumer Protection Law No. 8 of 1999 Article 8 Point c.Keywords: Goods Courier Wages System, Id Express Way Halim